Adaptive fault-tolerant control for longitudinal motion of supercavitating vehicles. (January 2021) - Bai, Yuliang; Biggs, James D.; Zhang, Zichen; Ding, Yibo
Abstract: A supercavitating underwater vehicle uses gas or vapor to reduce its skin friction enabling it to travel up to speeds of 200 m/s. However, traveling at extreme speeds can be challenging for control design since sudden disturbances or faults, even for a short time, can lead to large deviations from the reference trajectory. This paper addresses the problem of controlling a supercavitating vehicle which incorporates the actuator constraints and loss of effectiveness of the cavitator. An adaptive control law is designed based on the backstepping control method which includes an adaptive fault-tolerant component. The bounded adaptive update law can estimate the upper bound of the unknown total uncertainties including those induced by actuator faults. The proposed control is shown to guarantee stability in the presence of faults by using Lyapunov theory.